Differences in The Practice of Qunut Before and After Rukuk: Analytical Studies in the Shafi'i, Maliki, and Hanbali Schools - Arofah, Fajriyatul; Ghazali Said, Imam (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This research aims to examine the differences in the practice of the qunut prayer before and after the bowing (rukuk) in prayer based on the views of the three main Islamic jurisprudence schools, namely the Shafi'i, Maliki, and Hanbali schools. This study also explores the historical background, legal arguments, and the relevance of the practice in the context of contemporary Islamic worship. The research approach used is qualitative with a library research. The purpose of this descriptive-comparative study was to identify the similarities and differences among the three schools of thinking about qunut practice. The results of the extensive inquiry show that, although qunut is not recommended in the Hanbali school, it is done during the Fajr prayer before rukuk in the Maliki school and after rukuk in the Shafi'i school. This analysis concludes that variations in qunut practice are significantly influenced by historical contexts and hadith interpretations. Future research should concentrate on how social dynamics and regional norms affect the acceptance and use of qunut in contemporary Muslim communities.